The diversity of insects in polyculture farms, Palangka Raya, Central Kalimantan, Indonesia - Yanti, Rina; Mauliani, Nina; Yulianingsih, Kiki; Ningsih, Febry Claudia; Abrar, Muhammad; Adam, Chaidir; Haryono, Agus; Savitri, Shanty (Univeritas Papua, 2023)
Polyculture farming is an agricultural practice of growing several types of crops on the same land.The sustainability of polyculture farming is influenced by the presence of insects, both ecologically beneficial and detrimental. In agricultural ecology, insects have an important role as pollinators, predators, and pests that significantly affect the health of agricultural crops, including in polyculture farms. As an effort for sustainable polyculture management, especially in pest control, an exploratory study with mixed methods was conducted to determine the diversity, distribution, and categories of insects based on their ecological roles. This study was conducted in an agricultural area with a polyculture system in Palangka Raya, Central Kalimantan, Indonesia. A total of 12 insect species were identified from polyculture farms belonging to the orders Coleoptera, Diptera, Hemiptera, Lepidoptera, and Hymenoptera. The diversity of insects found in polyculture farming in this study was categorized into low diversity with a Shannon-Wiener index (H') of 2.186. Hemiptera is known to be the most abundant with 7 species identified. Based on the number of individuals, Componotus japonicus is the most abundant species with 9 individuals. The structure of the insect community based on their ecological role in polyculture farming consisted of 58.33% insect pests, 33.33% predatory insects, and 8.33% pollinating insects.